Hubungan Kebiasaan Membaca dan Penguasaan Kosakata Dengan Kemampuan Memahami Bacaan - Farida S (UHAMKA Graduate School Thesis Abstract Collection, 2016)
The research entitled correlation of reading habit and vocabulary to reading comprehension abilities, aims to determine whether there is a significant correlation between the habit of reading and vocabulary to reading comprehension abilities. This research is research that examines two independent variables on the dependent variable. Two independent variable questions are the habit of reading (X1) and vocabulary (X2), while the reading comprehension ability is the dependent variable (Y), therefore this study using a quantitative approach to the correlation technique. Data were collected using the instruments is shaped in the form of a questionnaire scale and a test, developed by researchers multiple choice with four (4) options. Results of this study can be seen in the data analysis consisting of a data description with each variable of research, testing analytical requirements, hypothesis testing and discussion of research results, once held hypothesis testing results show that the three hypotheses are significant correlated. Result show that (1) there is a positive correlation between the habit of reading with reading comprehension ability; (2) there is a positive correlation between vocabulary to reading comprehension ability; (3) there is positive correlation between the habit of reading and vocabulary equal to the ability to understand the reading.